The Influence of Problem Based Learning Models on the Ability to Write Dramatic Texts for Class VII Students of SMP Negeri 3 Pagaran - Sannur Hayati Sinaga (PT Inovasi Pratama Internasional, 2022)
The problem of this research is the Influence of Problem-Based Learning Models on the Ability to Write Dramatic Texts for Class VII Students of SMP Negeri 3 Pagaran. This study aims to determine the effect of problem-based learning models on the ability to write drama texts for seventh grade students of SMP Negeri 3 Pagaran. In carrying out the research, the research sample for class VII-4 was determined, which amounted to 36 people. The method used in this study is the experimental method of one group pre-test and post-test design pre-test. After the normality test and homogeneity test were carried out, it was known that the L count was 0.13 using = 0.05 and N = 36, then the critical value through the Liliefors test obtained L label 0.1456. Thus, L count < L table is 0.13 < 0.1456. This shows that the data before using the problem-based learning model above is normally distributed. From the results of the homogeneity test , it is obtained that F count = 1.06 with dk as the numerator of 36, and from the F distribution table and from the F distribution table for = 0.05, the F table value is 1.78. So F count < F table , ie 1.06 < 1.78 and it can be concluded that the research sample comes from a homogeneous population.